Time management skills in relation to general self-efficacy and parental sense of competence in individuals with and without cognitive disabilities - Hayat Roshanai Afsaneh; Janeslätt Gunnel; White Suzanne; Lidström Holmqvist Kajsa (Cogent Psychology, 2019)
Purpose The aim of the study was to investigate to what extent time management skills are associated with general self-efficacy and parental sense of competence, and if there are any differences between individuals with and without cognitive disabilities in these aspects. Material and Methods: The study had a comparative cross-sectional design. Totally 86 individuals with cognitive disabilities (of whom 31 were parents), and 154 without disabilities (of whom 68 were parents) were included (N = 240). The Swedish versions of the Assessment of Time Management Skills (including time management, organisation & planning, and regulation of emotion subscales), General Self-Efficacy, and Parental Sense of Competence scale (including satisfaction, efficacy, and interest subscales) were used to collect data. Results: There were significant differences (p < .001) between individuals with and without cognitive disabilities in all three subscales of Assessment of Time Management Skills and in General Self-Efficacy. Overall, individuals with a cognitive disability scored lower than persons without cognitive disabilities. A significant difference was observed between parents in all three subscales of time management skills after controlling for age and education (p < .0005). Parents with cognitive disabilities, compared to parents without cognitive disability, scored significantly lower in all measured scales, except for the interest subscale. In parents with a cognitive disability, there was a significant correlation between all three subscales of Time Management Skills and satisfaction. Among parents without a cognitive disability there was a significant correlation between time management; and organisation & planning subscales; and efficacy, and between General Self-Efficacy and time management. Conclusions: Poor time management, planning and organisational skills, as well as a deficit in regulation of emotions may have a negative impact on general self-efficacy and parental sense of competence.